Construction of metal (Mn, Ce, Eu)-containing species in CN nanocomposites with photo-responsive oxidase-mimicking activity for multi-antioxidant discrimination. (18th March 2022) - Du, Fan; Zhou, Xiaojie; Bai, Yilian; Tang, Qing; Cai, Yunfei; Tang, Yurong
Abstract : On the basis of three M-CN nanocomposites with photo-oxidase activity, a colorimetric sensor is proposed for the pattern recognition of antioxidants. Abstract : In this work, we construct three metal (Mn, Ce, Eu)-containing species in carbon nitride (CN) nanocomposites through a KCl template-assisted surface modification strategy. This newly developed approach not only uses a growth template to tailor the CN nanostructure but also modulates its electronic structure by metal coordination, resulting in M-CN with extended visible adsorption, increased dispersity, accelerated charge carrier separation and improved photocatalytic activity. Surprisingly, the proposed nanocomposites (Mn-CN, Ce-CN and Eu-CN) show outstanding photo-responsive oxidase-mimicking activity, with more than 5-fold improved activity compared with pristine g-C3 N4 during colorimetric sensing. Kinetic analysis reveals that these three photo-oxidase mimics possess a high affinity for chromogenic substrates due to a lower K m and higher V max than those of natural horseradish peroxidase. On the basis of the three proposed M-CN catalysts, a reliable colorimetric sensor array for the pattern recognition of antioxidants has been proposed. The different groups and diverse reduction abilities of the antioxidants, coupled with the different affinity between the antioxidants and catalysts, simultaneously enable the generation of unique cross-reactive response patterns, thus realizing discrimination for seven antioxidants with 100% accuracy. This sensor array has been successfully applied in discriminating seven antioxidants at different concentrations and in mixtures with different molar ratios, as well as in human urine samples, demonstrating the practicability of the sensor array. This developed approach promises a strategy to modify nanomaterials through nanostructure design, as well as a new route for colorimetric sensor arrays.